Between Conflict and Peace: The Government Policies and Sunni-Shia Relationship in Sampang and Yogyakarta - Ahmad Zainal Abidin; Imam Fuadi; Nur Kholis; Thoriqul Aziz (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2020)
The Shi’a minority encounters different kind of treatments from the Sunni majority in several regions in Indonesia; some falls into series of violent discriminative conflicts, while the other live in peace. The Sampang Shi’a community has encountered the first kind of treatments, whereas the Shi’a community in Yogyakarta is able to get a safe environment. The disjuncture comes from the different policies enacted by the respective regional governments. This study tries to describe the differences of the policies from the regional governments and uncover the factors structuring them. In doing so, this qualitative study approaches the issue through a case study using the theory of conflict proposed by Ralf Dahrendorf and functional theory of Lewis A. Coser. This study finds some factors leading to the different form of treatments of Sunnī majority towards the Shi’a minorities of Sampang and Yogyakarta, including: social, cultural, political, economic, and some other external factors. Furthermore, it also suggets that to cope with the discrimination issue towards the minority, the government could consider to implement the politics of multiculturalism proposed by Charles Taylor.